Impact of Formulation Variables on Meloxicam spanlastics Preparation - Sabri, Lubna; Khalil, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2024)
Spanlastic is a modern drug delivery that combines vesicular and nanoparticulate characteristics with numerous advantages over topical applied conventional vesicular systems in terms of stablility, penetration flexibility, and targeting. Meloxicam (MX) is a potent non-steroid anti-inflammatory drug that is frequently utilized for the short- and long-term treatment of chronic pain and inflammatory diseases including rheumatoid arthritis. However, the oral administration of MX often includes several adverse effects, including gastrointestinal disturbances and ulceration. Thus, the aim is a preparation of proper formula for MX-loaded spanlastics via studying the formulation variables that may affect their properties using the ethanol injection method. Variables include; span®60: edge activator ratio, the type of edge activators, the amount of MX, and the type of organic phase solvent were studied for their impact on particle size, polydispersity index, and entrapment efficiency. The formula that was selected showed sustained release for six hours, entrapment efficiency of 70.66±1.15%, zeta potential (-4.51), and particles that were 495±9.9 nm in size. Overall, the results indicated that spanlastics had the potential carrier for medicine delivery systems.